Hog cholera virus: molecular composition of virions from a pestivirus. - Thiel, H J (1991)
Virions from hog cholera virus (HCV), a member of the genus Pestivirus, were analyzed by using specific antibodies. The nucleocapsid protein was found to be a 14-kDa molecule (HCV p14). An equivalent protein could also be demonstrated for virions from another pestivirus, bovine viral diarrhea virus. The HCV envelope is composed of three glycoproteins, HCV gp44/48, gp33, and gp55. All three exist in the form of disulfide-linked dimers in virus-infected cells and in virions; HCV gp44/48 and gp55 each form homodimers, whereas gp55 is also found dimerized with gp33. Such complex covalent interactions between structural glycoproteins have not been described so far for any RNA virus.